Immune Dysfunctions and Immune-Based Therapeutic Interventions in Chronic Lymphocytic Leukemia - Griggio, Valentina; Perutelli, Francesca; Salvetti, Chiara; Boccellato, Elia; Boccadoro, Mario; Vitale, Candida; Coscia, Marta (Frontiers in Immunology, 2020)
Chronic lymphocytic leukemia (CLL) is a B-cell malignancy characterized by a wide range of tumor-induced alterations, which affect both the innate and adaptive arms of the immune response, and accumulate during disease progression. In recent years, the development of targeted therapies, such as the B-cell receptor signaling inhibitors and the Bcl-2 protein inhibitor venetoclax, has dramatically changed the treatment landscape of CLL. Despite their remarkable anti-tumor activity, targeted agents have some limitations, which include the development of drug resistance mechanisms and the inferior efficacy observed in high risk patients. Therefore, additional treatments are necessary to obtain deeper responses and overcome drug resistance. Allogeneic hematopoietic stem cell transplantation (HSCT), which exploits immune-mediated graft-versus-leukemia effect to eradicate tumor cells, currently represents the only potentially curative therapeutic option for CLL patients. However, due to its potential toxicities, HSCT can be offered only to a restricted number of younger and fit patients. The growing understanding of the complex interplay between tumor cells and the immune system, which is responsible for immune escape mechanisms and tumor progression, has paved the way for the development of novel immune-based strategies. Despite promising preclinical observations, results from pilot clinical studies exploring the safety and efficacy of novel immune-based therapies have been sometimes suboptimal in terms of long-term tumor control. Therefore, further advances to improve their efficacy are needed. In this context, possible approaches include an earlier timing of immunotherapy within the treatment sequencing, as well as the possibility to improve the efficacy of immunotherapeutic agents by administering them in combination with other anti-tumor drugs. In this review, we will provide a comprehensive overview of main immune defects affecting patients with CLL, also describing the complex networks leading to immune evasion and tumor progression. From the therapeutic standpoint, we will go through the evolution of immune-based therapeutic approaches over time, including i) agents with broad immunomodulatory effects, such as immunomodulatory drugs, ii) currently approved and next-generation monoclonal antibodies and iii) immunotherapeutic strategies aiming at activating or administering immune effector cells specifically targeting leukemic cells (e.g. bi-or tri-specific antibodies, tumor vaccines, chimeric antigen receptor T cells and checkpoint inhibitors).